2021
DOI: 10.1016/j.ejphar.2021.174268
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent administration sodium valproate has a protective effect on bone health in ovariectomized rats

Abstract: Objective: the present work was aimed to evaluate the effect of different administration modes of sodium valproate(VPA) on bone strength, bone mass and bone mineral density in ovariectomized(OVX) rats and further investigation of the possible mechanism.Methods: 60 female SD rats were randomly divided into 4 groups: Sham group (Sham, n=15), OVX group (OVX, n=15), OVX rats received intermittent VPA treatment group(IVPA, n=15) and OVX rats received daily VPA treatment group(EVPA, n=15). After 12 weeks of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In vitro experimental studies have reported that VPA regulates cell histone acetylation to accelerate osteoblast differentiation and the maturation processes [ 13 , 14 ]. Interestingly, several cellular and our previous animal experiment have shown VPA’s beneficial effects on bone health [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experimental studies have reported that VPA regulates cell histone acetylation to accelerate osteoblast differentiation and the maturation processes [ 13 , 14 ]. Interestingly, several cellular and our previous animal experiment have shown VPA’s beneficial effects on bone health [ 15 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…18 This could be particularly beneficial for patients with osteoporosis or those at risk of fractures, as it could potentially improve their bone health and reduce the risk of fractures. 30 On the other hand, VIT may have a negative effect on osteoclast activity, which is essential for bone resorption. 21 By inhibiting osteoclast function, VIT could potentially lead to an imbalance in bone metabolism, with a decrease in bone resorption rates.…”
Section: Discussionmentioning
confidence: 99%
“…These femurs were incubated in 10% EDTA (pH 7.4) at 4 °C for 4 weeks before paraffin-embedding. The longitudinally oriented bone defect sections with 4-µm-thick were collected for HE staining and immunohistochemical staining as previously described [ 19 , 32 ]. In brief, histological examination of decalcified sections were performed by staining with HE for light microscopy.…”
Section: Methodsmentioning
confidence: 99%